Integrating Gamification, Digital Literacy, and Local Wisdom into a Framework for Strengthening Digital Tolerance in Indonesia - Riyan Al Fajri (Journal of General Education and Humanities, 2025)
This study aims to enhance digital tolerance in Indonesia by developing an integrated framework for religious literacy. It responds to fragmented and ineffective approaches that fail to create a constructive digital environment for interfaith dialogue and unity. Employing a systematic literature review verified through the CRAAP method, this research synthesizes insights from multidisciplinary studies to construct a model based on three pillars: gamification to enhance youth engagement with moderation values; digital literacy to develop critical and reflective online behavior; and local wisdom as a cultural filter for strengthening social resilience. Findings indicate that the integration of these three elements fosters an interactive, inclusive, and culturally grounded digital ecosystem that supports interfaith understanding and mitigates radicalism. The study concludes that cross-sector collaboration between government, educational institutions, and religious organizations is essential for effective implementation. This conceptual model provides a strategic foundation for building a tolerant and harmonious digital society aligned with Pancasila’s principles.